The influence of stereochemically active lone-pair electrons on crystal symmetry and twist angles in lead apatite-2H type structures - Baikie, Tom (2016)
Lead-containing (Pb-B-X)-2H apatites encompass a number of [AF ]4[AT ]6[(BO4)6]X 2 compounds used for waste stabilization, environmental catalysis and ion conduction, but the influence of the stereochemically active lone-pair electrons of Pb2+ on crystal chemistry and functionality is poorly understood. This article presents a compilation of existing structural data for Pb apatites that demonstrate paired electrons of Pb2+ at both the AF and AT results in substantial adjustments to the PbFO6 metaprism twist angle, ϕ. New structure refinements are presented for several natural varieties as a function of temperature by single-crystal X-ray diffraction (XRD) of vanadinite-2H (ideally Pb10(VO4)6Cl2), pyromorphite-2H (Pb10(PO4)6Cl2), mimetite-2H/M (Pb10(As5+O4)6Cl2) and finnemanite-2H (Pb10(As3+O3)6Cl2). A supercell for mimetite is confirmed using synchrotron single-crystal XRD. It is suggested the superstructure is necessary to accommodate displacement of the stereochemically active 6s2 lone-pair electrons on the Pb2+ that occupy a volume similar to an O2– anion. We propose that depending on the temperature and concentration of minor substitutional ions, the mimetite superstructure is a structural adaptation common to all Pb-containing apatites and by extension apatite electrolytes, where oxide ion interstitials are found at similar positions to the lone-pair electrons. It is also shown that plumbous apatite framework flexes substantially through adjustments of the Pb F O6 metaprism twist-angles (ϕ) as the temperature changes. Finally, crystal-chemical [100] zoning observed at submicron scales will probably impact on the treatment of diffraction data and may account for certain inconsistencies in reported structures.